2022
DOI: 10.1002/sd.2415
|View full text |Cite
|
Sign up to set email alerts
|

Investing green for sustainable development without ditching economic growth

Abstract: Global warming and other significant climatic changes arising from the accumulation of carbon dioxide and other greenhouse gases have placed great policy puzzles on whether to slow or not to slow gross domestic product (GDP) growth. This paper presents and estimates empirical models of growth using standard tools of growth empirics for 23 OECD countries over the period 1990-2017. The main objective is to examine the role of green energy consumption and investment on economic growth. Using the Method of Moments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 133 publications
(205 reference statements)
2
22
1
Order By: Relevance
“…It has commonly been argued in the degrowth strategy that economic growth cannot occur alongside environmental protection (Kallis et al, 2012; Kang & Lee, 2021). Given the negative environmental effects of economic growth, the question commonly asked is whether to prioritise the environment by slowing down growth (Balcilar et al, 2022). It has however also been pointed out that trying to achieve environmental protection at the expense of economic growth could be counterproductive.…”
Section: Introductionmentioning
confidence: 99%
“…It has commonly been argued in the degrowth strategy that economic growth cannot occur alongside environmental protection (Kallis et al, 2012; Kang & Lee, 2021). Given the negative environmental effects of economic growth, the question commonly asked is whether to prioritise the environment by slowing down growth (Balcilar et al, 2022). It has however also been pointed out that trying to achieve environmental protection at the expense of economic growth could be counterproductive.…”
Section: Introductionmentioning
confidence: 99%
“…The application of the incentive system mitigated the partial rise in production costs (Figure 4b). The use of subsidized photovoltaic energy resulted in a partial decrease in production costs of 6.0%, which could be amplified by the increase in energy prices due to the political instability in Eastern Europe and the Honoré et al, 2019;Martos-Pedrero et al, 2022) and in other sectors, such as energy (Balcilar et al, 2022).…”
Section: Statistical Treatmentmentioning
confidence: 99%
“…Nevertheless, there is still no economic study that has evaluated the impact of eco‐innovations available for intensive agriculture, although it is known that some techniques can influence the decrease of production costs (i.e., self‐management of agricultural waste biomass) (Castillo‐Díaz, Belmonte‐Ureña, Batlles‐Delafuente, et al, 2022; Castillo‐Díaz, Belmonte‐Ureña, Camacho‐Ferre, et al, 2022). In other sectors, the use of eco‐innovations, research spending, and R&D development have small but positive effects on economic growth (Balcilar et al, 2022), something that has not yet been achieved in the Almeria model.…”
Section: Introductionmentioning
confidence: 99%
“…Having observed that a standard deviational ellipse provides a dynamic evolution patterns of residential energy consumption, suggested that electricity should be prioritised in the development of residential energy for growth. Balcilar et al (2022a) examine the effect of green energy consumption and investment on economic growth in OECD countries within the framework of the standard tools of growth empirics. The results revealed that although the effect of green energy is positive and significant but Rafindadi et al Journal of Economic Structures (2022) 11:27 their impacts on growth are small and heterogeneous across times.…”
Section: Literature Reviewmentioning
confidence: 99%